2017
DOI: 10.1038/s41467-017-00844-6
|View full text |Cite
|
Sign up to set email alerts
|

Direction-specific interaction forces underlying zinc oxide crystal growth by oriented attachment

Abstract: Crystallization by particle attachment is impacting our understanding of natural mineralization processes and holds promise for novel materials design. When particles assemble in crystallographic alignment, expulsion of the intervening solvent and particle coalescence are enabled by near-perfect co-alignment via interparticle forces that remain poorly quantified. Here we report measurement and simulation of these nanoscale aligning forces for the ZnO(0001)-ZnO(000) system in aqueous solution. Dynamic force spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 58 publications
4
95
0
Order By: Relevance
“…Classical surface charge-force models in a liquid medium [such as Derjaguin-Landau-Verwey-Overbeek (DLVO)] need to be extended to encompass nonspherical particle shapes and the molecular-level details that give rise to steric, hydration, and ion correlation forces between particles (111,112). Direct measurements of interparticle forces in controlled environments with very high precision are now possible (113,114). Present-day molecular simulations can encompass aspects of directionspecific nanomaterial interactions in aqueous solutions, such as predicting potentials of mean force for direction-specific interactions (113,115).…”
Section: New Opportunities For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical surface charge-force models in a liquid medium [such as Derjaguin-Landau-Verwey-Overbeek (DLVO)] need to be extended to encompass nonspherical particle shapes and the molecular-level details that give rise to steric, hydration, and ion correlation forces between particles (111,112). Direct measurements of interparticle forces in controlled environments with very high precision are now possible (113,114). Present-day molecular simulations can encompass aspects of directionspecific nanomaterial interactions in aqueous solutions, such as predicting potentials of mean force for direction-specific interactions (113,115).…”
Section: New Opportunities For Researchmentioning
confidence: 99%
“…Direct measurements of interparticle forces in controlled environments with very high precision are now possible (113,114). Present-day molecular simulations can encompass aspects of directionspecific nanomaterial interactions in aqueous solutions, such as predicting potentials of mean force for direction-specific interactions (113,115). However, much remains unknown about the fundamental basis for oriented versus nonoriented aggregation and homo-versus heteroaggregation.…”
Section: New Opportunities For Researchmentioning
confidence: 99%
“…The properties of related water layers depend on the surface properties of the substrate and are typically very different from those of macroscopically thick films. In such a form, water does not only contribute to the conversion of oxide surface layers into hydroxides, it can also act as a two‐dimensional solvent, which drives the alignment of oxide particles and enables the spontaneous structural and microstructural transformation of particle systems under ambient conditions …”
Section: Introductionmentioning
confidence: 99%
“…For example, in an important non-classical pathway for mineral growth-oriented attachment of nanoparticles-interfacial water ordering appears to play an important guiding role in the establishment of matching crystal lattice orientations between mineral grains required for fusion [54]. Indeed, Zhang et al [55,56] showed that the self-organization of intervening water between two approaching zinc oxide particles is critical for establishing a rotational force between misoriented surfaces. Our work demonstrates that interfacial water is connected across all exposed particle surfaces.…”
Section: Discussionmentioning
confidence: 99%